Olyra saginata, a new species of bagrid catfish (Actinopterygii: Siluriformes) from northeastern India - Ng, Heok Hee; Lalramliana, Lalramliana; Lalthanzara, Hmar (Zootaxa, 2014)
Olyra saginata, new species, is described from the Kaladan [=Kolodyne] River system in Mizoram, northeast India. It differs from congeners in having the following unique combination of characters: interorbital distance 27.9–35.9% HL; 54–66 lateral-line pores; body depth at anus 10.5–12.0% SL; length of adipose-fin base 17.3–22.4% SL; adipose fin separate from upper principal caudal-fin rays; post-adipose distance 11.8–14.3% SL; caudal peduncle length 14.8–17.7% SL; and caudal peduncle depth 7.8–8.9% SL. The taxonomy of congeners is also briefly discussed.